Analisis Investasi Pengadaan Alat Berat Untuk Mencapai Target Produksi Batu Gamping 240.000 Ton/Tahun Dengan Metode NPV dan IRR Di PT. Anugrah Halaban Sepakat - Indi Monika; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2018)
In this research the planning of the requirement of gear-loader and conveyance tool that will be discussed is short-term planning for 5 years to the needs of digging tools using Volvo Excavator EC 210, Caterpillar 320 D and transport equipment using Nissan CW 340. At PT. Anugrah Halaban Agreed to the procurement of equipment for the procurement and the means of procurement is carried out ie direct purchase and lease-purchase of both methods used certainly have weaknesses and advantages respectively, for it required analysis of the most profitable way with the company PT. Anugrah Halaban Agreed in the procurement of dug-load and hauling tools. In this research, the amount of ownership cost and operational cost is different for each unit of equipment and also there are difference of ownership cost and operational cost for rented equipment with direct purchased equipment. Cash Flow obtained, then analyzed by using the method of Net Present Value (NPV) so it can be known whether the available alternative is feasible economically. For cash purchase alternatives from existing cash flow, the NPV value for cash purchase alternatives for each tool is CAT 320D for 6,658,401.81, Volvo EC 210 3,869,332.88 and Nissan CW 340 1,624,886.73 so that NPV 0, then the alternative is declared economically viable. And for the alternative lease from the existing cash flow obtained NPV value for alternative leases for each tool is to for CAT 320D for 6,098,28.65, Volvo EC 210 2,144,823.13 and Nissan CW 340 1,121,962.12 so that NPV 0, then the alternative is declared economically viable. From the research that has been done in getting the results of comparison of NPV and IRR analysis can be stated that the most advantageous tool procurement alternative to the condition of the company at this time is buy-directly because NPV buy is greater than NPV rent-purchase.Keywords: Investment, NPV, IRR, Heavy Equipment, Leasing